Monitoring of seasonal variations in ground temperature at the observation site of Lomonosov MSU - Frolov Denis; Rzhanitsyn German; Sokratov Sergey; Koshurnikov Andrey; Gagarin Vladimir (E3S Web of Conferences, 2023)
The paper considers the problem of monitoring seasonal variations of ground temperature in northern and mountainous areas in the light of ongoing climate changes. To study seasonal variations of ground temperature, a model site of the Moscow State University Meteorological Observatory was used with the ability to monitor air temperature, snow cover thickness, and ground freezing temperature and depth, which was a prototype of a system for monitoring the state of permafrost soils used in the Arctic and mountain territories. The paper presents the results of monitoring seasonal variations of ground temperature based on the results of numerical modelling of the propagation of seasonal fluctuations of ground temperature in 2014-2017 in MATLAB environment which are in good agreement with the thermometry data and, therefore, the developed calculation scheme shows fairly good simulation results. This makes it possible to use the calculation scheme to assess the thermal state of frozen grounds and the stability of foundations and buildings and linear constructions located on them in the conditions of the North and mountainous territories. Therefore, the presented methodology can serve as a good help for monitoring and preventing the destruction of the observed structures in the conditions of climate warming.